Innovation solutions based on creation, implementation and commercialization of digital technologies - Karenov, R.S.; Baimukhamedova , G.S. (BUKETOV BUSINESS REVIEW, 2019)
The current state of the digitalization process in the world and Kazakhstan is being studied. The central, integrative role of digitalization and related technologies in the Fourth Industrial Revolution is shown. It is substantiated that today the concept of economic activity based on digital technologies has been created. The assessment of the role and importance of modern digital technology is given, including the «Internet of things», augmented reality technologies, etc.; the intellectualization of production processes and systems through the use of artificial intelligence technologies (machine learning), increased computational capabilities and big data, including for diagnostic services; flexible automation, allowing to move to a new type of adaptive autonomous production, reaching the maximum levels of productivity with the use of advanced robotics, 3D printing, electronic-optical control systems, blockchain. It is concluded that the basis for modern transformations in the global economy was, on the one hand, the development and improvement of information technologies, the saturation of national economies with ICT goods and services, and on the other hand, the widespread use of mobile communications and the Internet — key infrastructure components of the postindustrial society. It is noted that digital technology in Kazakhstan is considered as the main way to the diversification of the national economy, its reorientation from the raw material to the industrial-service model. Key indicators of the state program «Digital Kazakhstan» are presented. It is proved that Kazakhstan needs a radical reconstruction of information technologies, a quick transition to digitalization, which will be facilitated by the implementation of the «Digital Kazakhstan» program.